Test scores, noncognitive outcomes, and the stereotyping of non-local students - Qinyue Luo; Huihua Xie (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
This study investigates the impact of teachers' stereotyping of non-local students in terms of both academic performance and noncognitive outcomes using a random assignment of Chinese middle school students to teachers. We find that biased beliefs against non-local students, particularly among Chinese teachers, negatively affect non-local students by decreasing academic performance and increasing behavioral problems, with no significant effects on local students. Mechanism analysis suggests that these negative outcomes result from reduced teacher engagement with non-local parents, weaker classroom integration, and diminished self-confidence among non-local students. The negative effects are especially pronounced for non-local boys while non-local girls show resilience by increasing their efforts. These results highlight the critical role of teachers' stereotyping in shaping disparities in human capital development between local and non-local students.
Keywords: I24; J15; J24; 330; Teachers' Stereotypes; Non-Local Students; Test Scores; Mental Stress; Behaviour Problems Index